Correlation Between Contractile Properties Of Quadriceps Muscle and Functional Performance in Runners With Patellofemoral Pain Syndrome - Menan Aliy Eldeen Mohamed Elmahdy; Abdulsalam , Mohammed Shawki Supervisor; Ayad , Khaled Elsayed Supervisor; Abdelrahman , Amira Metwally Supervisor (Cairo : Cairo University, Faculty of Physical Therapy, 2023)
Background : Long distance runners commonly complain from patellofemoral pain syndrome ( PFPS ) that limits their performance and return to sports. Abnormal neuromuscular control of the quadriceps has been suggested to contribute to abnormal patellar tracking and hence PFPS. Neuromuscular alterations are a major causal factor of primary and secondary injuries , and it is influenced by alteration in muscle morphology and neural activity , clinically.
Thesis Submitted in Partial Fulfillment for the Requirement for the Doctoral Degree in Physical Therapy for Musculoskeletal Disorders
Keywords: Running related musculoskeletal injures; Sports injuries; Patellofemoral Pain Syndrome; Tensiomayography; Functional Performance